2009
DOI: 10.1051/0004-6361/200912041
|View full text |Cite
|
Sign up to set email alerts
|

The large quasar reference frame (LQRF)

Abstract: Context. The large number and all-sky distribution of quasars from different surveys, along with their presence in large, deep astrometric catalogs, enables us to build of an optical materialization of the International Celestial Reference System (ICRS) following its defining principles. Namely: that it is kinematically non-rotating with respect to the ensemble of distant extragalactic objects; aligned with the mean equator and dynamical equinox of J2000; and realized by a list of adopted coordinates of extrag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Some 135 000 quasars from the Gaia initial quasar catalogue (GIQC; Andrei et al 2009Andrei et al , 2012Andrei et al , 2014 were included towards the end of the solution (phase E in Fig. 4).…”
Section: Auxiliary Quasar Solutionmentioning
confidence: 99%
“…Some 135 000 quasars from the Gaia initial quasar catalogue (GIQC; Andrei et al 2009Andrei et al , 2012Andrei et al , 2014 were included towards the end of the solution (phase E in Fig. 4).…”
Section: Auxiliary Quasar Solutionmentioning
confidence: 99%
“…The radio source is associated with a star-like object in the WHT images and listed as a quasar by Andrei et al (2009), but no redshift is reported. Source F is a compact source (but resolved in the 1280 and 610 MHz images) and has an optical counterpart in the WHT images.…”
Section: Figmentioning
confidence: 99%
“…The extra objects will therefore have aux EPC = 1 but idEPC = 0 as a source identification in the part of the IGSL. -LQRF -The CU3 early version of Large Quasar Reference Frame (Andrei et al 2009): this is a compilation of QSOs with precise positions produced as part of the Gaia auxiliary catalog development. For these objects we have defaulted to the LQRF positions and set the proper motions to zero because they are all confirmed QSOs.…”
Section: Source Catalogsmentioning
confidence: 99%